Evaluating the levels of Tumor Necrosis Factorα-, Interleukin-6 and Vascular endothelial growth factor in patients with Colorectal Cancer - Nadir, Fenik Ahmed; Ali, Zeyan Abdullah (Iraqi Journal of Science, 2023)
Cytokines are polypeptides with several functions that are produced by a variety of bodily cells. They are clinically significant for illness diagnosis, treatment, and prevention. Interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) are the most important cytokines for cell division and proliferation. Vascular endothelial growth factor (VEGF) is produced in excess in mesenchymal, epithelial, and especially in tumor cells. In this study the serum levels of IL-6, TNF-α and VEGF were detected for 41 colorectal cancer patients and 41 healthy control group at Nanakaly Hospital by comparing their serum concentrations for patients paining from colorectal carcinoma (CRC) with those of the control subjects. The result shows a significant increase in the cytokines TNF-α, IL-6 and VEGF in patients with CRC when compared with the healthy group. A significant positive correlation (p<0.0001) was found between TNF-α with IL-6 (r= 0.8200) and VEGF (r= 0.7305). According to this study, there is a direct correlation between CRC and blood levels of (TNF-a, IL-6, and VEGF). This suggests that these cytokines are crucial for the development and spread of colorectal cancer.